2020
DOI: 10.1108/jhr-09-2019-0203
|View full text |Cite
|
Sign up to set email alerts
|

Rate of uncontrolled blood pressure and its associated factors in patients with predialysis chronic kidney disease in Bali, Indonesia

Abstract: PurposeHypertension is a key determinant for the development and progression of chronic kidney disease (CKD). The purpose of this study is to assess the rate of uncontrolled blood pressure (BP) and identify its associated factors in patients with predialysis CKD in Bali, Indonesia.Design/methodology/approachA cross-sectional study was conducted among 165 patients who attended the nephrology clinic in a central public hospital in Bali. Data were obtained by measuring BP at threshold 130/80 mmHg, as well as coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
(60 reference statements)
2
4
0
Order By: Relevance
“…The study found that 63.2% of the participants were incapable of controlling their BP less than 130/80 mmHg. This finding was consistent with previous studies that demonstrated the uncontrolled BP rates among NDCKD patients were in the range of 63.7%-64.8% (Zhang et al, 2019;Dharmapatni et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The study found that 63.2% of the participants were incapable of controlling their BP less than 130/80 mmHg. This finding was consistent with previous studies that demonstrated the uncontrolled BP rates among NDCKD patients were in the range of 63.7%-64.8% (Zhang et al, 2019;Dharmapatni et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…However, no study was conducted among patients with NDCKD. In terms of genetic factors, mixed results were demonstrated regarding the association between gender and uncontrolled BP in prior studies conducted in different settings (Lee et al, 2017 ; Dharmapatni et al, 2020 ). It can be seen that inconsistent findings were found between alcohol consumption, smoking status, age, DM, gender, and uncontrolled BP in previous studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More than one third of the hypertensive patients enrolled in several other studies had poorly controlled hypertension [30][31][32]. Other studies conducted among hypertensive patients with chronic kidney disease found that more than 60% of the patients had uncontrolled BP [33,34]. These findings highlight the value of investigating the primary contributing variables of poor BP control in hypertensive patients with diabetes in order to create effective strategies for controlling BP and overcoming the challenges in obtaining such a target among these patients.…”
Section: Discussionmentioning
confidence: 91%